계획된 당뇨교육이 환자역할행위 이행에 미치는 영향 : 일부 종합병원 중심으로 - 이은자 (연세대학교 보건대학원, 1988)
[한글] 당뇨병은 대사성 질환으로 완전치유가 잘 안되며 치료의 효과가 없을 때는 급성 또는 만성의 합병증과 죽음을 초래하게 된다. 환자가 합병증을 예방하고 건강한 생활을 영위하기 위해서 환자 자신이 당뇨병, 식이요법, 약물요법, 운동요법 및 자가관리에 관해 잘 알고 있어야 할 뿐 아니라 지시된 요법을 잘 이행하는 것이 필수적이라 할 수 있다. 그러므로 본 연구는 국내 여러 종합병원에서 당뇨교실을 개설하여 운영하고 있는바 계획된 당뇨교육이 환자역할행위 이행에 미치는 영향과 이에 관련된 요인을 비교 연구하기 위하여 시도되었다. 연구방법은 유사실험연구로써 1987년10월23일부터 1988년3월28일까지 인천과 부천의 C대학 부속병원 두곳과 일 종합병원에 입원하여 당뇨치료를 받고 있는 환자를 대상으로 하였다. 실험군은 당뇨교실에 등록하여 계획된 당뇨교육을 3∼4회 받은후 사후조사를 시행하고 대조군은 퇴원후 3주에 사후조사를 시행하여 비교하였다. 연구도구는 독립변수, 매개변수, 종속변수를 측정하기 위해 구조화된 설문지를 사용하였다. 수집된 자료의 분석은 계획된 당뇨교육의 효과에 대한 가설 검정을 위하여 t-검정과 Pearson correlation으로 하였다. 그밖에 환자역할행위 이행에 영향을 주는 요인을 확인하기 위하여 t-검정, ANOVA로 분석하였고 환자역할행위 이행에 영향을 미치는 주요 예측인자를 파악하기 위해 Stepwise Multiple Regression을 사용하였다. 연구결과의 요약은 다음과 같다. 제1가설 : "당뇨교실에 등록하여 계획된 당뇨교육을 받은 집단이 교육을 받지 않은 집단보다 환자역할행위 이행정도가 높을 것이다."는 지지되었다.(t = 5.77, P<.001) 제2가설: "당뇨교실에 등록하여 계획된 당뇨교육을 받은 집단이 교육을 받지 않은 집단보다 질병에 대한 지식정도가 높을 것이다."는 지지되었다.(t = 4.94, P<.001) 제3가설 : "당뇨교실에 등록하여 계획된 당뇨교육을 받은 집단이 교육을 받지않은 집단보다 건강신념이 높을 것이다."는 지지되었다.(t = 2.49, P<.05) 제4가설: "당뇨에 대한 지식수준이 높을수록 환자역할행위 이행정도가 높을 것이다."는 지지되었다.(r = .5087, P≤.001) 제5가설 : "건강에 대한 신념이 높을수록 환자역할행위 이행정도가 높을 것이다."는 지지되었다.(r = .4060, P≤.001) 제6가설: "당뇨에 대한 지식수준이 높을수록 건강신념이 높을 것이다."는 지지되었다.(r = .3428, P<.05) 그러나 인구학적 변수와 구조적 변수는 환자역할행위 이행에 영향을 미치지 않았으며, 환자역할행위 이행에 가장 영향을 미치는 요인은 지식으로 25.9% 설명할 수 있었으며, 다음이 건강에 대한 신념으로 환자역할행위 이행을 증진시킬 수 있었으나 교육을 통한 지식과 신념의 변화로 환자역할행위 이행을 32%만 설명할 수 있으므로 그 외에 이행에 영향을 미칠 수 있는 요인을 연구해야 할 것으로 사료된다. [영문] This study examined the effect of programmed education on compliance with appropriate sick-role behavior in diabetic patients. The purpose was to improve patient compliance, health beliefs and knowledge about diabetes. The study objectives were to determine factors influencing compliance with appropriate sick-role behavior and the effect of programmed education on compliance with appropriate sick-role behavior, knowledge and health beliefs of diabetic patients. The subjects, consisting of 60 diabetic patients diagnosed in three hospital in Inchon and Puchon City, were divided into experimental and control groups. Data were gathered through interviews using questionnaires from October, 1987 to March, 1988. In the group receiving the programmed education, the diabetics received education about diabetes, diet therapy, drugs, self-care, injection of insulin, complications and physical therapy by a nurse, physician, dietician, and pharmaceutist for one-half hours every week through four weeks. Questionnaires were an adjusted form of Park's questionnaires done by the researcher and were tested for content reliability by Item Analysis: Cronbach's α for the instrument measuring the following variables was for patient compliance .68, for diabetic knowledge .72 and for health beliefs. 64. Analysis of data was done by t-test, ANOVA, Pearson correlation coefficients, Stepwise Multiple Regression Analysis and Paired-t test. The results of the study may be summarized as follows: 1. The effect of programmed education on compliance with appropriate sick-role behavior, on health beliefs and diabetic knowledge was confirmed. Significant differences was found for all the variables between the experimental and the control group before and after the experiment. The first hypothesis that programmed education will increase compliance level in diabetic patients was accepted.(t = 5.77, P<.001) The second hypothesis that programmed education will increase knowledge of diabetes in diabetic patients was accepted.(t = 4.94, P<.001). The third hypothesis that programmed education will improve health beliefs in diabetic patients was accepted.(t = 2.49, P<.05) The fourth hypothesis that the higher the diabetic knowlege, the higher the compliance with appropriate sick-role behavior in diabetic patients was accepted.(r = .5087, P≤.001) The fifth hypothesis that the higher the health beliefs, the higher the compliance with appropriate sick-role behavior in diabetic patients was accepted.(r = .4060, P≤.001). The sixth hypothesis that the higher the diabetic knowledge, the higher the health beliefs in diabetic patients was accepted.(r = .3428, P<.05) 2.Factors influencing perceived compliance were knowledge of diabetes and health beliefs.
보건학과/석사